Changes in cardiovascular function after venlafaxine but not pregabalin in healthy volunteers: a double‐blind, placebo‐controlled study of orthostatic challenge, blood pressure and heart rate. (16th August 2013) - Diaper, Alison; Rich, Ann S.; Wilson, Sue J.; Craig, Kevin; Dourish, Colin T.; Dawson, Gerry R.; Nutt, David J.; Bailey, Jayne E.
Abstract : It is generally thought that venlafaxine raises blood pressure at higher doses; however, some studies have found no effect or a decrease in blood pressure. The aim of this study was to evaluate the cardiovascular (CV) effects of 3 weeks of dosing with venlafaxine, pregabalin and placebo on young healthy adults. Fifty‐four participants, of mean age 23.1 years (sd 4.68), 29 male, were randomised into three parallel groups. Each group received one of the three drugs, dosed incrementally over a 3‐week period to reach daily doses of 150 mg/day venlafaxine and 200 mg/day pregabalin. Blood pressure sphygmomanometer measurements, heart rate measurements, and orthostatic challenges recorded continuously beat‐to‐beat were performed weekly over this period and 5 days after treatment cessation. Results showed resting systolic blood pressure (SBP) and resting and standing diastolic blood pressure (DBP) and heart rate (HR) were significantly raised by venlafaxine compared with the pregabalin and placebo groups. SBP drop on standing was larger, the resulting overshoot was smaller, and recovery was slower on venlafaxine. HR recovery was significantly impaired by venlafaxine. CV changes were observed after only 1 week of dosing at 112.5 mg/day. These effects of venlafaxine are likely to be due to its action of noradrenergic reuptake inhibition. Copyright © 2013 John Wiley & Sons, Ltd.